Cytological Diagnosis of Small Cell Carcinoma of Vagina - A Diagnostic Dilemma - B. R. Yelikar (Journal of Krishna Institute of Medical Sciences University, 2013)
Small cell carcinoma is a neuroendocrine tumour, mainly arises in lung accounting for 20%of cases. In extra pulmonary sites it accounts for 5% of cases. Among gynaecological malignancies it accounts for 1-2% of cases, common sites are cervix, endometrium, ovary, vagina, vulva in decreasing frequencies. Small cell carcinoma is extremely uncommon in vagina.There are only 26 cases reported in the literature. Here we are reporting 27 th case. Because of its rarity the chances of missing the diagnosis are more. Correct morphological identification, with immunohistochemical analysis is essential for definitive diagnosis which will be helpful in planning appropriate treatment.